Visual Elements Influence at the Facade of Historical Buildings in Jalan Panglima Sudirman Corridor Batu, Indonesia - Santosa, Herry; Wijaya, Budi Tri; Ernawati, Jenny (University of Merdeka Malang, 2019)
ABSTRACTThe city of Batu is one of the colonial cities with enormous historical significance. There are several heritage objects in the past that have become the city's cultural heritage. Jalan Panglima Sudirman is one of the corridors having the most heritage, namely in form of historic buildings. The appearance of historic buildings often gives an interesting visual impression on a street corridor. This study was to determine the effect of visual elements on the facade of historical buildings based on people's perceptions. Using quantitative methods, data was collected through field surveys combined with questionnaires. Respondents were randomly selected in the street corridor. Based on public perception, it has been shown that the appearance of the facade of a historic building is moderate to good. The architectural style and shape of the of historical buildingsâ€™ facade are the most influential elements playing an important role. These results were expected to be able to help the community and government in the effort to develop the historic area.Â DOI: https://doi.org/10.26905/lw.v11i2.3004